Assessing Global Frailty Scores: Development of a Global Burden of Disease-Frailty Index (GBD-FI) - O’Donovan, Mark (Int J Environ Res Public Health, 2020)
Frailty is an independent age-associated predictor of morbidity and mortality. Despite this, many countries lack population estimates with large heterogeneity between studies. No population-based standardised metric for frailty is available. We applied the deficit accumulation model of frailty to create a frailty index (FI) using population-level estimates from the Global Burden of Disease (GBD) 2017 study across 195 countries to create a novel GBD frailty index (GBD-FI). Standard FI criteria were applied to all GBD categories to select GBD-FI items. Content validity was assessed by comparing the GBD-FI with a selection of established FIs. Properties including the rate of deficit accumulation with age were examined to assess construct validity. Linear regression models were created to assess if mean GBD-FI scores predicted one-year incident mortality. From all 554 GBD items, 36 were selected for the GBD-FI. Face validity against established FIs was variable. Characteristic properties of a FI—higher mean score for females and a deficit accumulation rate of approximately 0.03 per year, were observed. GBD-FI items were responsible for 19% of total Disability-Adjusted Life Years for those aged ≥70 years in 2017. Country-specific mean GBD-FI scores ranged from 0.14 (China) to 0.19 (Hungary) and were a better predictor of mortality from non-communicable diseases than age, gender, Healthcare Access and Quality Index or Socio-Demographic Index scores. The GBD-FI is a valid measure of frailty at population-level but further external validation is required.